Anaemia in rheumatoid arthritis: can we afford to ignore it?. Issue 1031 (9th June 2011) - Bloxham, E; Vagadia, V; Scott, K; Francis, G; Saravanan, V; Heycock, C; Rynne, M; Hamilton, J; Kelly, C A
Abstract : Introduction: Anaemia is common in rheumatoid arthritis (RA). Clinicians may focus on rheumatological issues and assume anaemia of chronic disease (ACD). This study challenged this assumption and investigated the causes of anaemia in a large cohort of RA patients to assess its implications. Methods: The hospital where the study was conducted monitors regular full blood count and erythrocyte sedimentation rate (ESR) monthly in all RA patients on disease modifying drugs to assess efficacy and safety. A computerised system identifies and records abnormal results. The database for 2009 was interrogated to find all patients with two consecutive haemoglobin values <11 g/dl. Using a proforma, patients were defined as having iron deficiency anaemia (IDA), ACD, macrocytic anaemia (MCA) or another cause. All results of further tests investigating the anaemia were recorded. Results: Among 2000 RA patients on the system, 199 (10%) were identified as having anaemia over a year. Of these, 90 had IDA, 78 had ACD, 25 had MCA, and 6 had postoperative anaemia. Among 90 patients with IDA, investigations were performed in 53, with 23 normal. An explanation for IDA was found in 30: gastrointestinal bleeding in 25, gynaecological blood loss in 3, and urinary bleeding in 2. Among 78 patients with ACD, response to intensification of RA treatment occurred in 45, but erythropoietin therapy was required in 9. Within the 25 patients with MCA, 12 had unrecognised vitamin B12 deficiency, 4 drug induced changes, 3 myeloid malignancy, 2 hypothyroidism, and 2 alcoholism. Conclusions: Anaemia in RA is common, multifactorial, and potentially both serious and correctable. Established malignancy was present in 10 patients and premalignancy in a further 10 (10% of total). Treatable causes were commonly identified. Clinicians need to investigate the nature and cause of persistent anaemia, and must not assume it to be simply ACD without evidence.